Reforming China’s Securities Civil Actions: Lessons From U.S. PSLRA Reform and Taiwan’s Government-Sanctioned Non-Profit - Jian-Lin, Chen; Wang, Wallace Wen-Yeu (Columbia Journal of Asian Law, 2008)
How should securities law be enforced? Different jurisdictions have different preferences and beliefs regarding the enforcement of securities law. Continental Europe and other civilian jurisdictions tend to rely on public enforcement as the primary enforcement tool. China, where administrative and criminal liability dominate securities law, is no exception. China only recently introduced several civil liability provisions. Indeed, China has only allowed civil claims by groups of defrauded investors since 2002, and even then the cause of action is restricted to misrepresentation. Other restrictions include a prerequisite of administrative or criminal sanctions, and the requirement that all litigants be ascertained before trial. The limited enforcement efforts made by China’s overburdened regulatory authorities and the inadequacy of civil remedies have led some scholars, in China and abroad, to advocate the adoption of U.S.-style class action suits. U.S. class actions represent the opposite end of the spectrum from the Chinese system. U.S. courts have long recognized the importance of class actions as a supplement to government regulatory efforts. Class actions are seen as a useful procedure for achieving economies of scale in litigation, enhancing law enforcement, and deterring misconduct that will adversely affect the interests of multiple parties. Indeed, empirical studies have confirmed the value provided by the strong private enforcement environment prevalent in the U.S. Still, U.S. class actions are not without social costs and critics. A typical criticism is that the disproportionate number of frivolous actions brought reduces shareholder welfare on average. Common concerns by foreigners include the fear of “legal blackmail” (a “flood of litigation”) and conflicts of interest for attorneys (“entrepreneurial litigation). Perceived abuses by such lawyer-driven entrepreneurial litigation were so severe as to lead to the enactment of the Private Securities Litigation Reform Act (“PSLRA”) of 1995. PSLRA reform aimed to increase the role played by institutional investors by establishing the rebuttable presumption that the lead plaintiff is the person with the largest financial interest in relief. It is hoped that the greater financial interest for the lead plaintiff will provide sufficient incentive to supervise what had previously been often unrestrained lawyers’ self interest. But, another approach to the problem exists. Like most civilian jurisdictions, Taiwan relies primarily on public enforcement. However, Taiwan also employs a government-sanctioned non-profit organization, the Securities and Futures Investors Protection Center, to help mitigate inadequate public enforcement. This is essentially a hybrid approach, relying on a non-private/commercial institution, with some independence from the government, to fulfill the need for generating public goods. In this article, we examine all three approaches in an attempt to answer the question of how securities law might best be enforced in China. Part II sets out the context of China’s securities civil actions and highlights the shortcomings of the current regime. Limitations in both public and private enforcement regimes in China indicate that reform is necessary. Part III analyzes U.S. class actions as a possible model for China’s proposed reform. The merits and limitations of U.S. class actions are discussed, with particular attention to the current regime’s failure to achieve the goals of deterrence and compensation. This results from the misalignment of the interests of the lawyers driving such litigation with the public good. Just as pertinently, the enactment and implementation of PSLRA provides valuable insight into the inadequacies of the U.S. model, which China should try to avoid reproducing. Drawing on the latest empirical studies and scholarship on the PSLRA reform and implementation, Part III examines the surprising findings regarding the active role of public institutional investors (e.g., public pension funds) vis-à-vis private intuitional investors (e.g., mutual funds, insurance companies, and banks) and a shocking implication overlooked in those studies. The enactment of PSLRA confirms the interest misalignment problem operating in lawyer-driven entrepreneurial litigations. The implementation of PSLRA reveals that only public institutional investors are taking up the active role intended by PSLRA. This is due to the presence of public/social interest in the calculus of these public institutional investors, which also leads them to commence more socially beneficial litigations, such as targeting individual defendants who are actually responsible for fraud. Synthesizing these analyses, one must conclude that since the efficiency of lawyer-driven entrepreneurial litigation does not equal efficiency in producing public goods (deterrence and compensation), there is an important role to be played by institutions motivated at least partly by public interest, in private enforcement. These institutions are arguably no less efficient or effective in producing public goods. Building on this conclusion, we proceed in Part IV to discuss Taiwan’s approach of utilizing a government-sanctioned non-profit organization (“NPO”) to fill the gap between public and private enforcement. While the government can undeniably exert considerable influence on this government-sanctioned NPO, the NPO still enjoys some independence by virtue of its official legal status, independent funding source, and level of expertise. This independence, though limited, will help safeguard the interest of investors’ compensation from being offset or diverted by competing government interests. This will be particularly useful in the context of China, where government and regulatory authorities are hugely concerned with the stable development of the State-Owned Enterprises (“SOEs”). However, we also note that there is room for improvement in terms of the transparency and independence of this NPO. Drawing on the analysis of U.S. and Taiwanese models, we argue in part V that due to limitations in China’s current legal infrastructure, political and social considerations, and different rationales for civil actions, the U.S. model is unsuitable for Chinese reform. On the other hand, considering the lessons learned from the enactment and implementation of PSLRA reform in the U.S., and China’s political and social considerations, we propose that an improvised Taiwan-style model is what China should work toward. The Taiwanese model would allow China to maximize its limited judicial resources in its attempt to improve securities law enforcement. Since our focus is on the reform of China’s securities civil actions, we do not propose any concrete reform plans for the U.S. model. Nonetheless, we highlight in the conclusion some implications the implementation of PSLRA reform has for future U.S. reform. We do not disturb the long-held recognition of the importance and desirability of relying on private enforcement to supplement public enforcement. However, we also see a strong case for relying on non-government institutions motivated at least partly by public interest (whether a public pension fund or a government-sanctioned NPO) to supplement public and private enforcement.